Bornholm.: Ein Beitrag zur Landeskunde der dänischen Ostseeinsel - Blüthgen, Joachim (ERDKUNDE, 1975)
Bornholm is different from the other Danish islands as well as from neighbouring southern Sweden but combines on the other hand some physical and cultural 'traits of these regions'. Its position relatively far away from the Danish cultural and administrative centre of Copenhagen and its central situation in the Baltic explain many of its cultural and historical features. The article attempts to give a survey of the physical traits of Bornholm and their variations within the island. When describing the human geography special emphasis is laid on demographic and occupational questions and Bornholm's role as a flourishing tourist centre for Danes, Swedes, and Germans is considered.